Cross sectional observation of the effects of carbon disulphide on arteriosclerosis in rayon manufacturing workers. Issue 7 (July 1998) - Omae, K; Takebayashi, T; Nomiyama, T; Ishizuka, C; Nakashima, H; Uemura, T; Tanaka, S; Yamauchi, T; O'Uchi, T; Horichi, Y; Sakurai, H
Abstract : OBJECTIVE: A prospective cohort study was designed to clarify the relations between occupational exposure to carbon disulphide (CS2) and its effects on arteriosclerosis in workers in 11 Japanese rayon manufacturing factories. This report is a cross sectional baseline observation in the first study year. METHODS: Study subjects were 432 male rayon workers (mean (range) age 35.5 (19.1-47.8); duration of exposure 13.4 (0.3-29.0)) and 402 male referent workers (age 35.8 (18.9-49.8)). Exposure to CS2 was assessed by determining the concentration of 2-thiothiazolidine-4-carboxylic acid (TTCA) in urine. Mean (SD) TTCA was 3.42 (2.73) mg/g creatinine (Cr) (n = 422). About a quarter of the urine samples were > 5 mg/g Cr, a biological exposure index recommended by the American Conference of Governmental Industrial Hygienists. Health effects on arteriosclerosis were evaluated by measuring blood pressure, serum lipids, pulse wave velocity of the aorta, stiffness and blood flow of the carotid artery, and blood coagulation and fibrinolysis indices, and by use of brain magnetic resonance imaging, electrocardiogram (at rest and after exercise), ophthalmograph, and Rose's questionnaire. Information on potential confounding factors was collected by self administered questionnaire. RESULTS: Prevalence of microaneurysm of the retinal artery was significantly higher in workers exposed to CS2 (8.1%) than in referent workers (3.4%), and increased with age. Other examinations did not show any differences between the two groups even after allowance for confounding factors. CONCLUSIONS: Significant effects of CS2 on arteriosclerosis were not found in current rayon manufacturing workers, with the exception of induction of microaneurysm of the retinal artery.